From Variables to Conclusions: Analysis Three Indicators of Science Process Skills in High School Physics Learning - Pramitha, Sarah; Darmaji, Darmaji; Kurniawan, Dwi Agus (Integrated Science Education Journal, 2026)
Purpose of the study: This study aims to analyze the development of Science Process Skills (SPS) in high school physics learning through a systematic review of international research published between 2017 and 2025. Methodology: This study employed a Systematic Literature Review (SLR) design guided by the PRISMA. Data were collected through a structured literature search of two international academic databases, Taylor & Francis Online and SpringerLink. Using purposive sampling based on predefined inclusion and exclusion criteria, a total of 30 peer-reviewed journal articles were selected for analysis from an initial pool of 300 identified records. Data were analyzed using qualitative thematic analysis to identify research trends, dominant SPS indicators, and instructional approaches applied in high school physics education. Main Findings: The synthesis reveals that inquiry-based learning, project-based learning, and virtual laboratory approaches are the most consistently reported strategies for enhancing students’ science process skills. Among the three SPS indicators, identifying variables and analyzing data are most frequently emphasized, while drawing conclusions remains less explicitly developed. Strengthening SPS through these approaches improves students’ scientific reasoning, experimental accuracy, learning engagement, and motivation in physics learning. Novelty/Originality of this study: This study provides an updated and systematic synthesis of global research on science process skills development in physics education up to 2025. By mapping instructional strategies and SPS indicators across international contexts, this review offers new conceptual insights into how inquiry-based and technology-supported learning can foster sustainable scientific thinking and support students’ readiness to meet 21st-century learning demands.